The Impact of Opium Consumption on Blood Glucose, Serum Lipids and Blood Pressure, and Related Mechanisms - Najafipour, Hamid; Beik, Ahmad (Frontiers in Physiology, 2016)
Abstract Aim: Substance abuse has become a universal crisisin our modern age. Among illegal substances, opium and its derivatives have been ranked second in terms of usage after cannabis in the world. In many Asian regions, the use of opium enjoys a high social acceptance; hence, some common people and even medical practitioners believe that opium lowers blood glucose and pressure and treat dyslipidemia. How much this belief is scientifically justified? Method: The results of available studies on both humans and animals searched in different search engines up to mid-2016 were integrated (77 articles). Upon the findings we try to offer a more transparent picture of the effects of opium on the mentioned factors along with the probable underlying mechanisms of its action. Results: Taken together, a variety of evidences suggest that the consumption of opium has no scientific justification for amendment of these biochemical variables. The mechanisms proposed so far for the action of opium in the three above disorders are summarized at the end of the article. Short term effects seems to be mostly mediated through central nervous system (neural and hormonal mechanisms), but long term effects are often due to the structural and functional alterations in some body organs. Conclusion: Although opium may temporarily reduce blood pressure, but it increases blood glucose and most of blood lipids. Moreover its long term use has negative impacts and thus it aggravates diabetes, dyslipidemia and hypertension. Accordingly, it is necessary to inform societies about the potential disadvantages of unauthorized opium consumption.